The discipline and affection - Ferrand Seminario, Janice (2004)
The present article is an interdisciplinary and synthetic point of view about the discipline and affection, two ideas which have been studied from their etymological actual origins going through their conceptual evolution in time. Our culture has prevailed love, faith, and illusion in detriment of discipline. We think children should be educated in a discipline of life that could make it possible for them during their to discover and practice the Universal Principles such as Truth, Kindness, Unity, Sacrifice, Work, Sobriety, Self-discipline, and Altruism.